2013
DOI: 10.1007/s40534-013-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on wheel–rail dynamic interactions of side-frame cross-bracing bogie and sub-frame radial bogie

Abstract: Improving freight axle load is the most effective method to improve railway freight capability; based on the imported technologies of railway freight bogie, the 27 t axle load side-frame cross-bracing bogie and sub-frame radial bogie are developed in China. In order to analyze and compare dynamic interactions of the two newly developed heavy-haul freight bogies, we establish a vehicle-track coupling dynamic model and use numerical calculation methods for computer simulation. The dynamic performances of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The initial conditions for solving the mathematical model are zero [25][26][27][28]. This is justified by the fact that the calculation was carried out with the nominal parameters of the components of the supporting structure of a flatcar.…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
“…The initial conditions for solving the mathematical model are zero [25][26][27][28]. This is justified by the fact that the calculation was carried out with the nominal parameters of the components of the supporting structure of a flatcar.…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
“…To determine the dynamic load that acts on the removable module on the platform car, the calculation is carried out. In this case, jumping fluctuations are taken into account as the most common type of oscillations in car operation [16,17]. The estimation scheme of the platform car is shown in Fig.…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
“…A comparative study of the dynamic interaction of wheels with rails when using bogies with lateral frame cross-braces and a radial subframe bogie is carried out in [2]. It was found that the radial bogie of the subframe has the best characteristics of wheel-rail interaction.…”
Section: Fig 1 Y25 Bogie Modelmentioning
confidence: 99%